Comparative Proteomic Analysis of Cultured Suspension Cells of the Halophyte Halogeton glomeratus by iTRAQ Provides Insights into Response Mechanisms to Salt Stress - Wang, Juncheng; Yao, Lirong; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Lai, Yong; Si, Erjing; Ren, Panrong; Yang, Ke; Shang, Xunwu; Wang, Huajun (Frontiers in Plant Science, 2016)
Soil salinity severely threatens land use capability and crop yields worldwide. An analysis of the molecular mechanisms of salt tolerance in halophytes will contribute to the development of salt-tolerant crops. In this study, a combination of physiological characteristics and iTRAQ-based proteomic approaches was conducted to investigate the molecular mechanisms underlying the salt response of suspension cell cultures of halophytic Halogeton glomeratus. These cells showed halophytic growth responses comparable to those of the whole plant. In total, 97 up-regulated proteins and 192 down-regulated proteins were identified as common to both 200 and 400 mM NaCl concentration treatments. Such salinity responsive proteins were mainly involved in energy, carbohydrate metabolism, stress defense, protein metabolism, signal transduction, cell growth, and cytoskeleton metabolism. Effective regulatory protein expression related to energy, stress defense, and carbohydrate metabolism play important roles in the salt-tolerance of H. glomeratus suspension cell cultures. However, known proteins regulating Na+ efflux from the cytoplasm and its compartmentalization into the vacuole did not change significantly under salinity stress suggesting our existing knowledge concerning Na+ extrusion and compartmentalization in halophytes needs to be evaluated further. Such data are discussed in the context of our current understandings of the mechanisms involved in the salinity response of the halophyte, H. glomeratus.